Levosimendan’s Effects on Length-Dependent Activation in Murine Fast-Twitch Skeletal Muscle - Haug, Michael; Michael, Mena; Ritter, Paul; Kovbasyuk, Larisa; Vazakidou, Maria Eleni; Friedrich, Oliver (International Journal of Molecular Sciences, 2024)
Levosimendan’s calcium sensitizing effects in heart muscle cells are well established; yet, its potential impact on skeletal muscle cells has not been evidently determined. Despite controversial results, levosimendan is still expected to interact with skeletal muscle through off-target sites (further than troponin C). Adding to this debate, we investigated levosimendan’s acute impact on fast-twitch skeletal muscle biomechanics in a length-dependent activation study by submersing single muscle fibres in a levosimendan-supplemented solution. We employed our MyoRobot technology to investigate the calcium sensitivity of skinned single muscle fibres alongside their stress–strain response in the presence or absence of levosimendan (100 µM). While control data are in agreement with the theory of length-dependent activation, levosimendan appears to shift the onset of the ‘descending limb’ of active force generation to longer sarcomere lengths without notably improving myofibrillar calcium sensitivity. Passive stretches in the presence of levosimendan yielded over twice the amount of enlarged restoration stress and Young’s modulus in comparison to control single fibres. Both effects have not been described before and may point towards potential off-target sites of levosimendan.
CRIS-Team Scopus Importer:2024-06-21
Keywords: calcium sensitivity; levosimendan; MyoRobot; single muscle fibre; stress–strain

Polyol pathway links glucose metabolism to the aggressiveness of cancer cells - Schwab, Annemarie; Siddiqui, Aarif; Vazakidou, Maria Eleni; Napoli, Francesca; Böttcher, Martin; Menchicchi, Bianca; Raza, Umar; Saatci, Ozge; Krebs, Angela; Ferrazzi, Fulvia; Rapa, Ida; Dettmer-Wilde, Katja; et al. (Cancer Research, 2018)
Cancer cells alter their metabolism to support their malignant properties. In this study, we report that the glucose-transforming polyol pathway (PP) gene aldo-keto-reductase-1-member-B1 (AKR1B1) strongly correlates with epithelial-to-mesenchymal transition (EMT). This association was confirmed in samples from lung cancer patients and from an EMT-driven colon cancer mouse model with p53 deletion. In vitro, mesenchymal-like cancer cells showed increased AKR1B1 levels, and AKR1B1 knockdown was sufficient to revert EMT. An equivalent level of EMT suppression was measured by targeting the downstream enzyme sorbitol-dehydrogenase (SORD), further pointing at the involvement of the PP. Comparative RNA sequencing confirmed a profound alteration of EMT in PP-deficient cells, revealing a strong repression of TGF-? signature genes. Excess glucose was found to promote EMT through autocrine TGF-? stimulation, while PP-deficient cells were refractory to glucose-induced EMT. These data show that PP represents a molecular link between glucose metabolism, cancer differentiation, and aggressiveness, and may serve as a novel therapeutic target.
EVALuna2:10237

Thymidylate synthase drives the phenotypes of epithelial-to-mesenchymal transition in non-small cell lung cancer - Siddiqui, Mohammad Aarif; Gollavilli, Paradesi Naidu; Ramesh, Vignesh; Parma, Beatrice; Schwab, Annemarie; Vazakidou, Maria Eleni; Natesan, Ramakrishnan; Saatci, Ozge; Rapa, Ida; Bironzo, Paolo; Schuhwerk, Harald; Asangani, Irfan Ahmed; et al. (British Journal of Cancer, 2020)
Background: Epithelial-to-mesenchymal transition (EMT) enhances motility, stemness, chemoresistance and metastasis. Little is known about how various pathways coordinate to elicit EMT’s different functional aspects in non-small cell lung cancer (NSCLC). Thymidylate synthase (TS) has been previously correlated with EMT transcription factor ZEB1 in NSCLC and imparts resistance against anti-folate chemotherapy. In this study, we establish a functional correlation between TS, EMT, chemotherapy and metastasis and propose a network for TS mediated EMT. Methods: Published datasets were analysed to evaluate the significance of TS in NSCLC fitness and prognosis. Promoter reporter assay was used to sort NSCLC cell lines in TSHIGH and TSLOW. Metastasis was assayed in a syngeneic mouse model. Results: TS levels were prognostic and predicted chemotherapy response. Cell lines with higher TS promoter activity were more mesenchymal-like. RNA-seq identified EMT as one of the most differentially regulated pathways in connection to TS expression. EMT transcription factors HOXC6 and HMGA2 were identified as upstream regulator of TS, and AXL, SPARC and FOSL1 as downstream effectors. TS knock-down reduced the metastatic colonisation in vivo. Conclusion: These results establish TS as a theranostic NSCLC marker integrating survival, chemo-resistance and EMT, and identifies a regulatory network that could be targeted in EMT-driven NSCLC. [Figure not available: see fulltext.]
CRIS-Team Scopus Importer:2020-10-16

Thymidylate synthase is functionally associated with ZEB1 and contributes to the epithelial-to-mesenchymal transition of cancer cells - Siddiqui, Aarif; Vazakidou, Maria Eleni; Schwab, Annemarie; Napoli, Francesca; Fernandez-Molina, Cristina; Rapa, Ida; Stemmler, Marc; Volante, Marco; Brabletz, Thomas; Ceppi, Paolo (Journal of Pathology, 2017)
Thymidylate synthase (TS) is a fundamental enzyme of nucleotide metabolism and one of the oldest anti-cancer targets. Beginning from the analysis of gene array data from the NCI-60 panel of cancer cell lines, we identified a significant correlation at both gene and protein level between TS and the markers of epithelial-to-mesenchymal transition (EMT), a developmental process that allows cancer cells to acquire features of aggressiveness, like motility and chemoresistance. TS levels were found to be significantly augmented in mesenchymal-like compared to epithelial-like cancer cells, to be regulated by EMT induction, and to negatively correlate with micro-RNAs (miRNAs) usually expressed in epithelial-like cells and known to actively suppress EMT. Transfection of EMT-suppressing miRNAs reduced TS levels, and a specific role for miR-375 in targeting the TS 3'-untranslated region was identified. A particularly relevant association was found between TS and the powerful EMT driver ZEB1, the shRNA-mediated knockdown of which up-regulated miR-375 and reduced TS cellular levels. The TS-ZEB1 association was confirmed in clinical specimens from lung tumours and in a genetic mouse model of pancreatic cancer with ZEB1 deletion. Interestingly, TS itself appeared to have a regulatory role in EMT in cancer cells, as TS knockdown could directly reduce the EMT phenotype, the migratory ability of cells, the expression of stem-like markers, and chemoresistance. Taken together, these data indicate that the TS enzyme is functionally linked with EMT and cancer differentiation, with several potential translational implications. Copyright © 2017 Pathological Society of Great Britain and Ireland. Published by John Wiley & Sons, Ltd.
EVALuna2:10226

Thymidylate synthase maintains the de-differentiated state of triple negative breast cancers - Siddiqui, Aarif; Gollavilli, Paradesi Naidu; Schwab, Annemarie; Vazakidou, Maria Eleni; Ersan, Pelin G.; Ramakrishnan, Mallika; Pluim, Dick; Coggins, Siana A.; Saatci, Ozge; Annaratone, Laura; HM Schellens, Jan; Kim, Baek; et al. (Cell Death and Differentiation, 2019)
Cancer cells frequently boost nucleotide metabolism (NM) to support their increased proliferation, but the consequences of elevated NM on tumor de-differentiation are mostly unexplored. Here, we identified a role for thymidylate synthase (TS), a NM enzyme and established drug target, in cancer cell de-differentiation and investigated its clinical significance in breast cancer (BC). In vitro, TS knockdown increased the population of CD24 + differentiated cells, and attenuated migration and sphere-formation. RNA-seq profiling indicated repression of epithelial-to-mesenchymal transition (EMT) signature genes upon TS knockdown, and TS-deficient cells showed an increased ability to invade and metastasize in vivo, consistent with the occurrence of a partial EMT phenotype. Mechanistically, TS enzymatic activity was found essential for maintenance of the EMT/stem-like state by fueling a dihydropyrimidine dehydrogenase—dependent pyrimidine catabolism. In patient tissues, TS levels were found significantly higher in poorly differentiated and in triple negative BC, and strongly correlated with worse prognosis. The present study provides the rationale to study in-depth the role of NM at the crossroads of proliferation and differentiation, and depicts new avenues for the design of novel drug combinations for the treatment of BC.
CRIS-Team Scopus Importer:2019-08-30